Change of venue [large type] - Griffin, James J., 1949- (A Texas Ranger Rames C. Blawcyzk novel, 2023)
"Sixth generation Texas Ranger James C. Blawcyzk has ruffled the feathers of his superiors at Company F one time too many. He's offered a choice: Either transfer to Company E, and an isolated post in far west Texas, resign, or be terminated. Knowing he'd be a better fit in the wild, wide-open spaces of the Big Bend anyway, Jim accepts the transfer. He and his family prepare to pack up and move west. Any illusions Jim might have had about crime being less rampant in the Big Bend than the Austin area are soon shattered, starting with two men attempting to steal hay from his barn before his family has even settled in. Jim soon discovers he's facing not only corrupt politicians and police officers in Presidio County, but has landed in the middle of a deadly turf war between two rival gangs for control of the drug and human trafficking business in almost all of the Trans-Pecos. Jim will come close to death more than once as he fights the criminal elements. A final trackdown leads him into an ambush, deep in the wilderness of Big Bend Ranch State Park. Despite both himself and his horse being badly wounded, Jim vows to bring the men he's been trailing for days to justice, or die in the attempt. His only hope is to catch up with them before he succumbs to his wounds."--